2007
DOI: 10.1021/bm060926k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Poly[(organo)phosphazenes] with Cell-Adhesive Side Groups

Abstract: There is a need to develop new scaffold materials with controlled surface properties for tissue engineering applications. For that purpose novel biodegradable poly[(organo)phosphazenes] were synthesized. A cell-binding molecule, galactose, was introduced via a spacer, either 6-aminohexanol (AH) or poly(ethylene glycol) (PEG; M(w) = 3400). Some polymers were substituted with an additional PEG chain of different molecular weights (M(w) = 750 or 5000). The polyphosphazene derivatives were characterized by 1H NMR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…The reactions of hexachlorocyclotriphosphazatriene, N 3 P 3 Cl 6 , which is known as the standard compound in the field of phosphazene and polyorganophosphazene chemistry, [1][2][3][4][5] with bulky bifunctional reagents lead to the formation of spiro-, ansa-, spiro-ansa-, binoarchitectures and cyclolinear or cyclomatrix polymers. [6][7][8][9] The different substituents that are bonded to phosphorus atoms are very effective for the determination of the physical and chemical properties of new phosphazene derivatives and polyorganophosphazenes.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of hexachlorocyclotriphosphazatriene, N 3 P 3 Cl 6 , which is known as the standard compound in the field of phosphazene and polyorganophosphazene chemistry, [1][2][3][4][5] with bulky bifunctional reagents lead to the formation of spiro-, ansa-, spiro-ansa-, binoarchitectures and cyclolinear or cyclomatrix polymers. [6][7][8][9] The different substituents that are bonded to phosphorus atoms are very effective for the determination of the physical and chemical properties of new phosphazene derivatives and polyorganophosphazenes.…”
Section: Introductionmentioning
confidence: 99%
“…914-918). Furthermore, side-group modification with cell adhesive groups such as galactose using various spacers has resulted in a new class of polymers with increased protein interaction and biocompatibility (Heyde et al, 2007(Heyde et al, , 2008. This ability to create a large group of polymers with the required properties renders polyphosphazenes more versatile than some of the polymer systems available for tissue engineering applications.…”
Section: Polyphosphazenes and ''Tunability''mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Polyphosphazene derivatives with carbohydrates as side groups are of particular interest for probes or effectors in biological processes involving carbohydrate/protein interactions. [16][17][18][19][20][21][22][23] For example, Heyde et al introduced galactose to polyphosphazene using either 6-aminohexanol or poly(ethylene glycol) as a spacer, and demonstrated that the galactose pendants were able to selectively bind lectin. A large proportion of galactose was favorable for multivalent carbohydrate/protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of galactose was favorable for multivalent carbohydrate/protein interactions. [19,20] Yang et al synthesized galactosylated polyphosphazene with a 4.9% degree of substitution from poly{[2-(2-aminoethoxy)ethoxy]phosphazene} and lactobionic acid. [23] They found that the galactose pendants could be used as targeting ligands and showed specific affinity to the asialoglycoprotein receptor.…”
Section: Introductionmentioning
confidence: 99%